KAJIAN KARAKTERISTIK PEMBENTUK KENYAMANAN TERMAL PADA PASAR RAKYAT GIANYAR - Ida Bagus Trena Windu; Made Yudantini; Nyoman Susanta (Jurnal Arsitektur ARCADE, 2025)
Abstract: Traditional markets are public facilities that play an important role in supporting daily economic and social activities; therefore, thermal comfort within market buildings is an essential aspect that requires attention. In tropical humid regions such as Indonesia, high air temperature and relative humidity often lead to thermal discomfort in market buildings. This study aims to analyze the thermal comfort conditions of the Gianyar Traditional Market building and to evaluate its compliance with ASHRAE Standard 55-2017 and SNI 03-6572-2001. The research employed a quantitative method with a descriptive approach. Primary data were obtained through direct field measurements of thermal environmental parameters, including air temperature, relative humidity, air velocity, and mean radiant temperature, as well as questionnaires distributed to traders and visitors to assess thermal comfort perception. Thermal comfort analysis was conducted using the PMV Calculator V2 Modified to determine the Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) values. The results indicate that all floors of the Gianyar Traditional Market building fall within the neutral to slightly warm category and generally meet the comfort range specified by ASHRAE standards. User perception analysis shows that most traders and visitors feel comfortable performing their activities inside the market building. However, relative humidity levels on all floors exceed the recommended standard limits. Therefore, improvements in thermal comfort are required, particularly through humidity control strategies, such as the application of dehumidifiers and appropriate passive cooling systems that align with the characteristics of traditional market buildings. Keyword: thermal comfort, traditional market, PMV, ASHRAE 55, SNI 03-6572-2001. Abstrak: Pasar rakyat merupakan fasilitas publik yang memiliki peran penting dalam menunjang aktivitas ekonomi dan sosial masyarakat, sehingga kenyamanan termal di dalamnya perlu mendapat perhatian. Pada wilayah beriklim tropis lembap seperti Indonesia, suhu dan kelembapan udara yang tinggi sering menimbulkan ketidaknyamanan termal pada bangunan pasar. Penelitian ini bertujuan untuk menganalisis tingkat kenyamanan termal Gedung Pasar Rakyat Gianyar serta mengevaluasi kesesuaiannya terhadap standar ASHRAE Standard 55-2017 dan SNI 03-6572-2001. Metode yang digunakan adalah penelitian kuantitatif dengan pendekatan deskriptif. Data primer diperoleh melalui pengukuran langsung parameter lingkungan termal yang meliputi suhu udara, kelembapan udara, kecepatan angin, dan temperatur radiasi, serta melalui kuesioner persepsi kenyamanan termal kepada pedagang dan pengunjung. Analisis kenyamanan termal dilakukan menggunakan PMV Calculator V2 Modified untuk memperoleh nilai Predicted Mean Vote (PMV) dan Predicted Percentage of Dissatisfied (PPD). Hasil penelitian menunjukkan bahwa seluruh lantai Gedung Pasar Rakyat Gianyar berada pada kategori neutral hingga slightly warm dan secara umum masih termasuk dalam rentang kenyamanan menurut standar ASHRAE. Persepsi pengguna menunjukkan bahwa mayoritas pedagang dan pengunjung merasa nyaman beraktivitas di dalam gedung pasar. Namun demikian, parameter kelembapan udara pada seluruh lantai masih berada di atas batas standar yang ditetapkan. Oleh karena itu, diperlukan upaya peningkatan kenyamanan termal melalui pengendalian kelembapan udara, antara lain dengan penggunaan dehumidifier dan sistem pendinginan pasif yang sesuai dengan karakteristik bangunan pasar rakyat. Kata Kunci: kenyamanan termal, pasar rakyat, PMV, ASHRAE 55, SNI 03-6572-2001.